DEVELOPING STUDENTS' VOCABULARY MASTERY THROUGH HIDDEN OBJECT GAME - Ningsi, Gayatri; Darmawan, Darmawan; Wahyudin, Wahyudin (Tadulako University, 2024)
The objective of this research is to find out if the use of Hidden Object Game can develop vocabulary mastery to the eighth grade students of SMP Negeri 4 Palu. This research employed a quasi-experimental research design that involved experimental group and control group. The sample of this research was class VIII Apel with 33 students as the control group and class VIII Rambutan with 33 students as the experimental group, selected by using purposive sampling technique. The data was collected by administering a vocabulary test consisting of a pre-test and post-test. Then the treatment was only given to the experimental group. The result of the pre-test of the experimental group was 51.43 while the control group was 52.47. The result of the post-test of the experimental group was 81.73 while the control group was 68.74. The data were analyzed statistically in order to find out the significant difference of students' achievement in the pre-test and post-test by using the t-test formula. By applying 0.05 level of significance where the degree of freedom (df) is 64, the researchers found that the value of the t-counted (5.03) is higher than the t-table (1.99). It means that the research hypothesis is accepted. In conclusion, the use of Hidden Object Game can develop vocabulary mastery to the eighth grade students of SMP Negeri 4 Palu.